Peningkatkan Literasi Keuangan dan Transparansi Yayasan melalui Sistem Informasi Terintegrasi - KURNIAWATI, ESTETIKA MUTIARANISA; Sangka, Khresna Bayu; Chayati, Nur; Rizki , Saktiana (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
A foundation is a non-profit organization operating in the fields of religion and education, with its primary funding coming from public donations in the form of alms and charity. Although it is not intended to generate profit, a foundation must still address financial aspects and prepare financial reports in accordance with applicable standards to ensure accountability to the public. Good financial management involves budgeting, cash flow management, expense oversight, transparent financial reporting, and financial report analysis. The main issue faced by Yayasan Cipta Solo Berbagi is ineffective financial management, with financial reports being simple ledgers and not compliant with ISAK 35 standards. The Pustapako community service team collaborated with Yayasan Cipta Solo Berbagi to address this issue through a series of activities, including focus group discussions (FGDs), training, and the implementation of a web-based accounting information system. The results indicate that by applying appropriate accounting standards and using a suitable accounting information system, the foundation can produce more transparent, accurate, and comprehensible financial reports. The foundation's management now has improved capabilities in financial management, enhancing donor and public trust. This program also opens opportunities for similar programs in the future with more in-depth material and long-term support programs for foundations. Keywords: Non-profit foundation, financial management, financial reporting, ISAK 35, accountability, accounting information system, training, community service